(untitled) (Journal of Laboratory Animal Science, 2019)
The study was conducted to assess the hepatoprotective activity of Asteracantha longifolia in carbon tetra chloride (CCl4) induced hepatotoxicity in rats. The hepatoprotective effect of methanolic extract of whole plant of Asteracantha longifolia was studied by monitoring serum aspartate amino transferase (AST), serum alanine amino transferase (ALT) and histopathological alterations. Pre-treatment with methanol extract of Asteracantha longifolia in rats treated with CCl4 showed a significant inhibition (P<0.001) of rise in serum ALT and AST at all the doses tested (600, 900 or 1200 mg/kg). Histopathological studies provided the added evidence for biochemical analysis. Histopathological studies showed total recovery of liver damage caused by CCl4 on treatment with silymarin as well as Asteracantha and such treated groups showed very less hepatic damage with few areas of fatty changes. These studies revealed that the methanol extract of Asteracantha longifolia has potent hepatoprotective activity. It showed even better efficiency than the well known hepato protective agent silymarin in reducing the ALT and AST concentrations in CCl4 treated rats